2019
DOI: 10.1097/pec.0000000000000911
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Abuse Among Young Children With Rib Fractures

Abstract: Objectives We aimed to estimate the prevalence of abuse in young children presenting with rib fractures and to identify demographic, injury, and presentation-related characteristics that affect the probability that rib fractures are secondary to abuse. Methods We searched PubMed/MEDLINE and CINAHL databases for articles published in English between January 1, 1990 and June 30, 2014 on rib fracture etiology in children ≤ 5 years old. Two reviewers independently extracted predefined data elements and assigned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 40 publications
0
22
0
4
Order By: Relevance
“…Additionally, it reflects that awareness of child abuse is on the rise. However, some reports showed that the trend of child abuse was “not a true increase in prevalence but due to the changes in legislation” [ 25 , 26 ]. In another context, some researchers found that there were no changes in the rate of child physical abuse [ 27 , 28 ], even though there was a rise in the prevalence of child emotional abuse [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it reflects that awareness of child abuse is on the rise. However, some reports showed that the trend of child abuse was “not a true increase in prevalence but due to the changes in legislation” [ 25 , 26 ]. In another context, some researchers found that there were no changes in the rate of child physical abuse [ 27 , 28 ], even though there was a rise in the prevalence of child emotional abuse [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of rib fractures in the absence of a known traumatic event, pathological condition, or pertinent history, are considered highly suspicious of pediatric NAI. While no specific rib fracture number or location is pathognomonic for abuse, the general consensus in the clinical realm has been that posterior or posteromedial rib fractures are highly specific for abuse (Kleinman, 2015; Love et al, 2011; Paine, Fakeye, Christian, & Wood, 2019). However, a recent review study by Paine et al (2019) argues that for children younger than 4 years old, there is not enough current literature to support the argument that posterior rib fractures, compared to rib fractures in other locations, indicate an increased likelihood of abuse (Paine et al, 2019).…”
Section: Pediatric Skeletal Trauma Interpretation and The Contributiomentioning
confidence: 99%
“…1,8,11,30,31,33 Only specific diagnoses of abuse, or adverse social and parental circumstances preceding the date of first entry in the Out-of-home Care Register or within 15 days after that date, were categorized as exposure variables. Diagnoses of SDH, RH, rib fracture, or long bone fracture were selected that are claimed to have the highest positive predicative value for abuse, PPV of 0.69 for SDH, 9 0.97 for severe RH, 9 0.67 to 1.0 for rib fracture, 10,15,34 and 0.57 for long bone fracture. 11 Those diagnoses were combined in different categories and finally as one category, "SDH, RH, rib fracture, or long bone fracture" ( Table 1).…”
Section: Exposuresmentioning
confidence: 99%